Effects of mangroves and tidal flats on suspended‐sediment dynamics: Observational and numerical study of Darwin Harbour, Australia. Issue 9 (10th September 2014) - Li, Li; Wang, Xiao Hua; Andutta, Fernando; Williams, David
Abstract The suspended‐sediment dynamics in Darwin Harbour, Australia were investigated using field measurements and numerical modeling. The model suspended‐sediment concentration (SSC) agreed well with observation; the root‐mean‐square error was less than 0.02 kg m−3 and the anomaly correlation coefficient greater than 0.6. Model results indicate that the tide is the dominant forcing for suspended‐sediment transport: total sediment transport was seaward in the channel and landward at the East and Middle Arm entrances, dominated by the Eulerian residual current. Further numerical experiments indicate that mangroves and tidal flats play key roles in redistributing suspended sediment and affecting total sediment transport by modulating the tides and the tidal asymmetry. In Darwin Harbour, if these areas were reclaimed, there would be a significant transport of sediment into the inner harbor. However, the water in East Arm would be less turbid, with about 70% lower bottom SSC during spring tides. The landward sediment flux at its entrance would decrease by 99%, because of reduced currents in the Arm due to a weakened tidal choking effect. Tidal pumping would then dominate sediment transport in the channel and at the entrances of East and Middle Arms. Dredging for the East Arm Wharf affected the SSC upstream in East Arm. According to the model, material from dredging disposed of at a location outside the harbor will be transported back into the outer harbor, generating higher SSC values there. Although this study is site‐specific, the findings may be applicable to suspended‐sediment dynamics in other harbors and estuaries with extensive tidal flats and mangroves.